2004
DOI: 10.1038/sj.ijir.3901227
|View full text |Cite
|
Sign up to set email alerts
|

The ‘effectiveness’ scale—therapeutic outcome of pharmacologic therapies for ED: an international consensus panel report

Abstract: Despite availability of outcome measures and scales for assessing erectile dysfunction (ED) treatment efficacy, guidelines are not available for assessing broader therapeutic outcomes or defining treatment failure in ED. An International Consensus Advisory Panel was convened to develop guidelines, definitions and a new algorithm for evaluating treatment effectiveness in ED. These new guidelines are recommended for use in both research and clinical practice. A multidisciplinary, international panel, consisting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(40 citation statements)
references
References 6 publications
3
36
0
Order By: Relevance
“…34 It has been shown that 65% of prescriptions written in the United States for PDE5 inhibitors are from primary care clinicians. 35 Ideally, these clinicians will provide early encouragement to help couples select ED treatments to enhance emotional and physical intimacy and to identify those couples who may benefit most from a long-acting PDE5 inhibitor.…”
Section: The Clinician's Role In Ed Managementmentioning
confidence: 99%
“…34 It has been shown that 65% of prescriptions written in the United States for PDE5 inhibitors are from primary care clinicians. 35 Ideally, these clinicians will provide early encouragement to help couples select ED treatments to enhance emotional and physical intimacy and to identify those couples who may benefit most from a long-acting PDE5 inhibitor.…”
Section: The Clinician's Role In Ed Managementmentioning
confidence: 99%
“…Main reasons for nonresponse included inappropriate timing of sexual intercourse, single dose trial, and lack of titration to the highest recommended dose. Such data emphasize the need for regular follow-up and exploration of the self-reports of non-response; a patient should be considered as truly non-responder only after '4 sexual attempts with administration of the highest tolerated drug dose, in accordance with manufacturer's guidelines with respect to timing relative to meals, alcohol ingestion, use of concomitant medications, and adequate sexual stimulation/arousal' [73]. Furthermore, recent study clearly demonstrated that counseling may also convert "non-responders" to responders [74].…”
Section: Pde5i: Unanswered Questionsmentioning
confidence: 98%
“…Although the effectiveness of PDE5 inhibitors on such intermediate objective outcomes as penile rigidity through penile plethysmography with the RigiScan device (Dacomed Corporation, Minneapolis, MN, USA) has been studied, measuring the therapeutic effectiveness of tadalafi l is more accurately defi ned through an integration of the patient's reported treatment response and tolerability with the reported satisfaction of both the patient and his partner (Carson et al 2004b). Despite their intrinsically subjective nature, validated questionnaires are the preferred major outcome measure of treatment effectiveness of tadalafi l and other PDE5 inhibitors.…”
Section: Background On Outcome Measuresmentioning
confidence: 99%